Biomechanical Analysis of a Novel Double-Point Fixation Method for Displaced Intra-Articular Calcaneal Fractures - Lv, Miko Lin; Ni, Ming; Sun, Wanju; Wong, Duo Wai-Chi; Zhou, Shuren; Jia, Yongwei; Zhang, Ming (Frontiers in Bioengineering and Biotechnology, 2022)
Development of minimal invasive procedure and implant material have improved the fixation strength of implant yet less traumatic in the surgery. The purpose of this study was to put forward a novel “double-point fixation” for calcaneal fractures and compare its biomechanical stability with traditional “three-point fixation”. A three-dimensional finite element foot model with Sanders type IIIAB calcaneal fracture was developed based on clinical images, which comprised bones, plantar fascia, ligaments and encapsulated soft tissue. The double-point fixation and three-point fixation were resembled by the surgical procedure with the volar distal radius plate and calcaneal locking plate, respectively. The stress distribution, fracture displacement and change of Böhler angle and Gissane’s angle were estimated by a walking simulation using the model and the prediction between the double-point and three-point fixation were compared at heel-strike, midstance, and push-off instants. Double-point fixation demonstrated lower bone stress (103.3 vs. 199.4 MPa), but higher implant stress (1084.0 vs. 577.9 MPa). The model displacement of double-point was higher than that of three-point fixation(3.68 vs. 2.53 mm). The displacement of the posterior joint facet (0.127 vs. 0.150 mm), the changes of Bohler angle (0.9° vs. 1.4°) and Gissane’s angle (0.7° vs. 0.9°) in double-point fixation was comparably lower. Double-point fixation by volar distal radius plate demonstrated sufficient and favorable fixation stability and lower risk of post-operative stress fracture, which might potentially serve as a new fixation modality for the treatment of displaced intra-articular calcaneal fractures.